2014
DOI: 10.2527/jas.2014-7677
|View full text |Cite
|
Sign up to set email alerts
|

The effect of incremental levels of dietary nitrate on methane emissions in Holstein steers and performance in Nelore bulls1

Abstract: Two experiments were conducted to study effects of dietary nitrate on enteric methane production, blood methemoglobin concentration, and growth rate in cattle. In Exp. 1, 36 Holstein steers (288 ± 25 kg BW) were fed increasing levels of dietary nitrate (6 levels; 0 to 3.0% of feed DM) in corn silage-based total mixed rations. Nitrate was introduced gradually in a 25-d adaptation period before methane production was determined in environmentally controlled rooms. In the rooms, feed intake was restricted and sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 24 publications
6
38
2
1
Order By: Relevance
“…Only where nitrate was administered directly into the rumen (Takahashi et al, 1998;Sar et al, 2004) were greater MetHb concentrations than those found in the present study observed (34.3% and 18.37% in each of the studies, respectively), presumably because of transiently high concentrations of nitrite in the rumen generated by the method of administration. Recently, Newbold et al (2014) removed steers from an experiment because MetHb concentrations in excess of 20% were observed during adaptation to nitrate. Although most steers removed (eight of nine) were fed higher dietary nitrate concentrations (24 and 30 g nitrate/kg diet DM) than used in the present study, one steer removed was fed 18 g nitrate/kg diet DM.…”
Section: Discussionmentioning
confidence: 99%
“…Only where nitrate was administered directly into the rumen (Takahashi et al, 1998;Sar et al, 2004) were greater MetHb concentrations than those found in the present study observed (34.3% and 18.37% in each of the studies, respectively), presumably because of transiently high concentrations of nitrite in the rumen generated by the method of administration. Recently, Newbold et al (2014) removed steers from an experiment because MetHb concentrations in excess of 20% were observed during adaptation to nitrate. Although most steers removed (eight of nine) were fed higher dietary nitrate concentrations (24 and 30 g nitrate/kg diet DM) than used in the present study, one steer removed was fed 18 g nitrate/kg diet DM.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate, propynoic acid, and p-coumaric acid had much lower inhibitory effects on predicted in vivo CH 4 production. Nitrate is reported to be an effective CH 4 production mitigating dietary component [49,50]. For example, a 24.8% reduction in CH 4 production by lactating cows receiving nitrate at 21.1 g NO 3 − /kg of DM was observed by Olijhoek et al [51].…”
Section: Dietary Strategies To Decrease Ch 4 Production From Ruminantsmentioning
confidence: 97%
“…At the same time, nitrite produced as an intermediary product of DNRA would have a direct toxic effect toward methanogenic Archaea (Klüber and Conrad, 1998; Asanuma et al, 2015). Nitrate decreased CH 4 production in lactating dairy cows (21 g nitrate/kg dry matter [DM], −23.4% CH 4 ; Olijhoek et al, 2016), steers (30 g nitrate/kg DM, −29.4% CH 4 ; Newbold et al, 2014) and sheep (20 g nitrate/kg DM, −16.5% CH 4 ; de Raphélis-Soissan et al, 2014). Nitrooxypropanol is a synthetic compound developed by DSM Nutritional Products Ltd (Kaiseraugst, Switzerland).…”
Section: Introductionmentioning
confidence: 99%